Teaching and Learning With Body Mapping Online Using Digital Tools: Navigating Methodological Vulnerability and Insights for Future Development - Anna CohenMiller; Aigul Rakisheva (International Journal of Qualitative Methods)
How can body mapping—traditionally practiced with physical materials in face-to-face settings—be effectively adapted for teaching and learning in online spaces using digital tools? This question drives our exploration of body mapping as an online method within arts-based research (ABR) and pedagogy. We emphasize directions for teaching about how to use and implement this approach with the aim of creating equitable, inclusive, and justice-centered practices. This article examines our experiences designing and facilitating an online workshop that introduced participants to body mapping using digital tools, drawing on diverse contexts, including our lived experiences teaching body mapping in Kazakhstan and the United States. Through embodied critical self-reflection and poetic inquiry, we navigate the vulnerabilities and “messiness” inherent in qualitative methods, uncovering a process for adapting body mapping for online environments with open access, collaborative, digital art tools. Our exploration highlighted the challenges of transitioning from a tactile and embodied method to a virtual platform. While our process of teaching others how to use body mapping online with digital tools was imperfect and uncomfortable at times, the process offers methodological potential for continued exploration and application. As such, we offer insights into embracing discomfort and provide tangible adaptations for teaching body mapping as a participatory and emancipatory research method.